قصة سليمان-عليه السلام- مع الهدد في ضوء علم اللغة النفسي (دراسة صوتية) - Dr sumaira Saghir ahmed; Asifa Mariam (التراث الأدبي, 2025)
This study presents a psycho-phonetic analysis of the story of Solomon (peace be upon him) and the hoopoe, as narrated in the Holy Qur’an. It draws upon the field of psycholinguistics, which explores the connection between language and human emotions, and examines how sounds contribute to the expression of feelings and psychological connotations.